2000
DOI: 10.1046/j.1468-2982.2000.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on the Risk of Ischaemic Stroke Associated With Use of Combined Oral Contraceptives and Hormone Replacement Therapy in Women With Migraine

Abstract: We suggest strategies for the use of combined oral contraceptives (COCs) and hormone replacement therapy (HRT) in women with migraine, based on available evidence, when it exists, and expert opinion. They do not set a standard, since migraine management and stroke prevention require a¯exible and individualized approach, the evidence is low grade (expert appraisal of the literature with peer review (Grade C, see notes)), and no randomized controlled clinical trials exist. They do not replace general guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 0 publications
0
68
0
Order By: Relevance
“…390,402 • For those who choose to use OCs despite the increased risk associated with their use, aggressive therapy for stroke risk factors may be reasonable (Class IIb; Level of Evidence C). 390,392,402 Diet and nutrition • Reduced intake of sodium and increased intake of potassium as indicated in the report Dietary Guidelines for Americans are recommended to lower BP (Class I; Level of Evidence A).…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…390,402 • For those who choose to use OCs despite the increased risk associated with their use, aggressive therapy for stroke risk factors may be reasonable (Class IIb; Level of Evidence C). 390,392,402 Diet and nutrition • Reduced intake of sodium and increased intake of potassium as indicated in the report Dietary Guidelines for Americans are recommended to lower BP (Class I; Level of Evidence A).…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…Our data support previous studies that reported an increase in stroke risk associated with smoking and the use of OCs among young women 11,16,18,21 and clinical recommendations to modify these risk factors in the presence of migraine with aura. 32,33 There were 145 ischemic stroke patients among women with PMVA. When we stratified our analyses by ischemic stroke subtype, we found that PMVA was associated with strokes of undetermined origin and showed a strong trend toward an association with lacunar stroke, which is more a descriptive than an etiologic category.…”
Section: Discussionmentioning
confidence: 99%
“…5 The combination of oral contraceptives and migraine with aura increases the risk of ischemic stroke 5-to17-fold. 6 Our patient also had recent infection and increased stress, which may have contributed to a prothrombotic state. Importantly, none of these factors by themselves are sufficient to explain the patient's stroke.…”
Section: Martinez Majander Et Al Cryptic Loss Of Consciousness E165mentioning
confidence: 73%